Endovascular Treatment in the Subclavian Steal Syndrome: Series of 29 Patients - Gatto, Luana Antunes Maranha; Seabra, Diego do Monte Rodrigues; Zenatti, Gabriel Angelo Garute; Frose, Letícia; Koppe, Gelson Luis; Demartini, Zeferino, Junior (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Subclavian steal syndrome is a group of symptoms resulting from retrograde flow in the vertebral artery, “stealing” blood from the posterior intracranial circulation and other territories, caused by stenosis or occlusion of the subclavian artery proximal to the origin of the same vertebral artery, or even of the brachiocephalic trunk. Most of the time, it is an incidental finding in patients with other conditions or cerebrovascular risk factors. We report a series of 29 patients with an angiographic diagnosis, in which 7 received treatment (all endovascular), all with symptoms directly related to this condition. Advanced age, systemic arterial hypertension, diabetes mellitus, smoking and stroke were comorbidities frequently related. Six patients improved completely after the procedure and one remained with vertigo.
Keywords: subclavian steal syndrome; arteriography; left side; angioplasty